2015
DOI: 10.4238/2015.may.4.3
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 polymorphism 509 C>T is associated with an increased risk for hepatocellular carcinoma in HCV-infected patients

et al.

Abstract: ABSTRACT. Transforming growth factor-beta 1 (TGF-β1), a member of the transforming growth factor beta family, functions as a multi-functional cytokine and plays a key role in cellular growth, proliferation, and differentiation. The 509 C/T polymorphism in the TGF-β1 gene has been implicated in the outcome of hepatitis C virus (HCV) infection; however, little is known regarding the relationship between TGF-β1 gene mutations and the development of hepatocellular carcinoma (HCC) in HCV-infected patients. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…There were 1,427 HCC cases and 3,735 controls, and all studies were hospital-based. In studies by Falleti et al [14], Qi et al [15], Radwan et al [16], Xin et al [17], and Shi et al [18], the control genotype distributions were in Hardy-Weinberg equilibrium, but they were not in the studies by Saxena et al [19] and Ma et al [20]. In the Kim et al study [13], it could not be determined whether the genotype distribution of the controls was in Hardy-Weinberg equilibrium because the TT and CT genotypes were counted as a single group.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…There were 1,427 HCC cases and 3,735 controls, and all studies were hospital-based. In studies by Falleti et al [14], Qi et al [15], Radwan et al [16], Xin et al [17], and Shi et al [18], the control genotype distributions were in Hardy-Weinberg equilibrium, but they were not in the studies by Saxena et al [19] and Ma et al [20]. In the Kim et al study [13], it could not be determined whether the genotype distribution of the controls was in Hardy-Weinberg equilibrium because the TT and CT genotypes were counted as a single group.…”
Section: Resultsmentioning
confidence: 96%
“…Of the four studies including HBV-infected subjects, three indicated a significant association between TGF-β1 C-509T variants and decreased HCC susceptibility [13,15,17,19]. However, two studies using HCV-infected subjects suggested a significant association between TGF-β1 C-509T variants and increased HCC susceptibility [16,20]. Thus, it is possible that an overall meta-analysis using integrated data that include subjects with HBV-related CLD and those with HCV-related CLD may mask the opposite tendencies between them, in terms of the TGF-β1 C-509T variants and HCC susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the predefined inclusion criteria, 10 out of 86 retrieved articles were qualified for analysis [7, 16, 17, 1925] and the selection process is schematized in Figure 1. As two articles from within included sub-studies according to the co-infection of hepatitis B and C viruses [16, 17], a total of 12 studies were qualified for the association of TGFB1 gene C-509T polymorphism with hepatocellular carcinoma, involving 2809 patients with hepatocellular carcinoma and 4802 cancer-free controls.…”
Section: Resultsmentioning
confidence: 99%
“…TGFB1 gene is polymorphic in genomic sequences and it incorporates approximate 1700 validated bi-allelic polymorphisms. One of the most widely-evaluated polymorphisms is C-509T (rs1800469) in the promoter region of TGFB1 gene and this polymorphism was reported to be associated with the significant changes of circulating TGF-β1 by many investigators [16, 17]. What's more, experimental evidence from reporter constructs suggested that expression of TGFB1 gene differed significantly between the -509C allele and the -509T allele, and this difference may be caused by selective activator protein 1 (AP1) recruitment to its promoter [18].…”
Section: Introductionmentioning
confidence: 99%